Policy Learning, Policy Failure, and the Mitigation of Policy Risks: Re-Thinking the Lessons of Policy Success and Failure. Issue 7 (August 2022) - Leong, Ching; Howlett, Michael
Policy failures are often assumed to be unintentional and anomalous events about which well-intentioned governments can learn why they occurred and how they can be corrected. These assumptions color many of the results from contemporary studies of policy learning which remain optimistic that ongoing policy problems can be resolved through technical learning and lesson drawing from comparative case studies. Government intentions may not be solely oriented toward the creation of public value and publics may not abide by government wishes, however, and studies of policy learning need to take these "darksides" of policy-making more seriously if the risks of policy failure are to be mitigated.